A severe case of ichthyophthirius multifilis infection in Rainbow Trout - ΠΝΕΥΜΑΤΙΚΑΤΟΣ, Γ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The author described, for the first time in Greece, a case of a severe form of Ichthyophtirius infection (I. Multifilis), in rainbow trout observed in a unit of trout culture. According his findings, concluded that the disease, at least in young fish, causes a high mortality indirectly,.because of the coexistance of gill disease. In opposite, in adult fish the mortality is low, but it is sure that the disease causes a retardation of grouth